Intended Consequences : Birth Control, Abortion, and the Federal Government in Modern America. - Critchlow, Donald T. (Oxford University Press, 2001)
After World War II, U.S. policy experts--convinced that unchecked population growth threatened global disaster--successfully lobbied bipartisan policy-makers in Washington to initiate federally-funded family planning. In Intended Consequences, Donald T. Critchlow deftly chronicles how the government's involvement in contraception and abortion evolved into one of the most bitter, partisan controversies in American political history. The growth of the feminist movement in the late 1960s fundamentally altered the debate over the federal family planning movement, shifting its focus from population.